2012
DOI: 10.1111/apt.12043
|View full text |Cite
|
Sign up to set email alerts
|

eHealth: individualisation of infliximab treatment and disease course via a self‐managed web‐based solution in Crohn's disease

Abstract: SUMMARY BackgroundInfliximab (IFX) maintenance therapy for Crohn's disease (CD) is administered every 8 weeks, but inter-patient variation in optimal treatment intervals may exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 37 publications
1
69
0
1
Order By: Relevance
“…Recognizing the shortcomings of CDAI (such as impracticability and the inherent deviations arising from recall bias in data collection), and the importance of disease monitoring in CD, several published studies have used a self-reporting symptom collecting tool, using an electronic diary or web-based system to assess symptoms in patients with CD [15,17]. The study by Litcher-Kelly et al reported the feasibility of an electronic diary for collecting symptoms using software installed on a handheld computer [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recognizing the shortcomings of CDAI (such as impracticability and the inherent deviations arising from recall bias in data collection), and the importance of disease monitoring in CD, several published studies have used a self-reporting symptom collecting tool, using an electronic diary or web-based system to assess symptoms in patients with CD [15,17]. The study by Litcher-Kelly et al reported the feasibility of an electronic diary for collecting symptoms using software installed on a handheld computer [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not establish detailed parameters for the diary, and the sample size was very small (n = 16). Recently, a web-based telemanagement system has been introduced for patients with IBD, which has encouraged the active involvement of patients in the assessment and treatment of their disease [14,15]. The open-label pilot study reported the efficacy, and safety, of a web-based approach for the maintenance of infliximab treatment for patients with CD, suggesting that this novel method might be a promising concept for the individualization of infliximab treatment in IBD [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations